A closer look at the physical and optical properties of gold nanostars: an experimental and computational study. Issue 11 (7th March 2017) - Tsoulos, T. V.; Han, L.; Weir, J.; Xin, H. L.; Fabris, L.
Abstract : TEM-reconstructed 3D topography was used for the first time to determine the plasmonic properties of gold nanostars via finite element simulations. Abstract : A combined experimental and computational study was carried out to design a semi-empirical method to determine the volume, surface area, and extinction coefficients of gold nanostars. The values obtained were confirmed by reconstructing the nanostar 3D topography through high-tilt TEM tomography and introducing the finite elements in COMSOL Multiphysics through which we have also calculated the morphology-dependent extinction coefficient. Doing so, we have, for the first time, modeled the heat losses of a real, experimentally synthesized nanostar, and found the plasmon resonances to be in excellent agreement with those obtained experimentally. We believe that our approach could substantially improve the applicability of this remarkable nanomaterial.